Evaluating Methods for Aflatoxin B1 Monitoring in Selected Food Crops Within Decentralized Agricultural Systems - Haadia Tanveer; Hannah Glesener; Blake Su; Brooke Bolsinger; Rosa Krajmalnik-Brown; Lee E. Voth-Gaeddert (Toxins)
Aflatoxin B1 (AFB1) contamination of food crops pose severe public health risks, particularly in decentralized agricultural systems common in low-resource settings. Effective monitoring tools are critical for mitigating exposure, but their adoption is limited by barriers such as cost, infrastructure, and technical expertise. The objectives of this study were: (1) to evaluate common AFB1 detection methods, including enzyme-linked immunosorbent assays (ELISA) and lateral-flow assays (LFA), validated via high-performance liquid chromatography (HPLC), focusing on their suitability for possible applications in decentralized, low-resource settings; and (2) to conduct a barriers-to-use assessment for commonly available AFB1 detection methods and their applicability in low-resource settings. Among four ELISA kits, the AgraQuant Aflatoxin B1 2/50 ELISA Kit demonstrated the highest accuracy and precision, reliably quantifying AFB1 in maize and tortillas across 5–150 ppb with minimal cross-reactivity. For LFA, a smartphone-based algorithm achieved a high presence/absence accuracy rate of 84% but struggled with concentration prediction. The barriers-to-use analysis highlighted the practicality of low-cost tools like moisture readers for field screening but underscored their qualitative limitations. Advanced methods like HPLC and LC-MS offer greater precision but remain impractical due to their high costs and infrastructure requirements, suggesting a potential role for adapted ELISA or LFA methods as confirmatory approaches. These findings support the development of multi-tiered frameworks integrating affordable field tools with regional or centralized confirmatory testing. Addressing systemic barriers through capacity building, partnerships, and improved logistics will enhance AFB1 monitoring in decentralized systems, protecting public health in vulnerable communities.